PRINSIP MOST FAVOURED NATIONS DAN PENGECUALIANNYA DALAM WORLD TRADE ORGANIZATION (WTO) - FX. Joko Priyono (Masalah-Masalah Hukum, 2013)
Most Favoured Nations principle require the WTO members for not doing discrimination to products from other WTO members for both tariff bound products and non tariff bound products. This principle is the heart of GAIT, GATS dan TR/Ps. Thing that relevant in term of implementation of the principle is like product application which is examined in certain cases either in the panel level or in the Appelate Body level. Nevertheless, there are exceptional clauses for not applying the principle. They are Article XX, XX/, XXIV dan XXV(5) in which Article XX(b) and (g) are often used by WTO members as a reasonable grounds to protect human, animal, plant life or health and to protect exhaustable natural